Tele-SPACE: group parent-based treatment for pediatric anxiety via telemedicine in a public health clinic - de la Fontaine, Naama; Cohen, Tal; Hertz-Palmor, Nimrod; Dorman-Ilan, Shirel; Rubin, Noa; Itav, Gal; Tsafrir, Shlomit; Carmel, Yael; Weisman, Hana; Gothelf, Doron; Lebowitz, Eli R. (Frontiers in Psychiatry, 2025)
IntroductionSupportive Parenting for Anxious Childhood Emotions (SPACE) is an evidence-based treatment for parents of children with anxiety disorders and/or obsessive-compulsive disorder (OCD). Given the many barriers to accessing such evidence-based treatments, we evaluated for the first time the application of group-based SPACE, delivered to parents via telemedicine within a public health outpatient setting.MethodsIn this single arm retrospective analysis of routine-care data participants, recruited from a hospital-based anxiety clinic, were mothers (N=50) of fifty children, ages 6.7-18.0 years (mean 11.2 ± 3.1), diagnosed with an anxiety disorder and/or OCD. Parent and child self-report measures assessed the impact of treatment on child anxiety symptoms, parental accommodation, parental anxiety and depression. Treatment feasibility, acceptability and satisfaction were assessed.ResultsPost treatment, significant reductions were evident in child self-reported separation anxiety symptoms (p =0.008), mother-reported child anxiety symptoms (p=0.002), maternal accommodation (p=0.006), anxiety (p=0.004) and depressive symptoms (p=0.011). Treatment proved feasible, with completion rates of 77.3%, and participants reported high levels of satisfaction with the telemedicine format.DiscussionThis is the first study of group-based SPACE over telemedicine. Results support the utility of this modality for overcoming treatment barriers in public health settings with highly heterogenous populations.